534 ADVANCED COMMUNICATION SKILLS: TEACHING DURING A PANDEMIC. (14th June 2021) - Pedersen, A; Greenhalgh, M; Tan, M; Terry, R; Royle, C; Royles, K
Abstract: Introduction: In the first wave of the COVID-19 pandemic, it was recognised there would be an increased demand on clinicians to provide patients and relatives with bad news. The national ban on hospital visiting rapidly changed the way in which this news would be delivered. In recognition of these new challenges, our team sought to design a teaching course that could be implemented quickly and cost effectively, with the aim of improving clinician's confidence around these difficult skills. Methods: A teaching programme was created using senior geriatric and palliative care clinicians as simulated patients, open to any grade and speciality. Learners were required to break bad news (BBN) without any visual feedback, to simulate skills required when using the telephone. Surveys were collected to determine self–assessed confidence across four domains (Table 1) before, immediately after and 4–20 weeks after the course. Participants were asked to rank their confidence for each skill on a 5 point scale with 1 being very unsure and 5 being very confident. Results: Pre-teaching scores showed an average of 3 (neither confident nor unsure) across all domains. After the course all domains improved, most notably around discussing end of life (EoL) care and discussing information over the phone. Conclusion: This project has highlighted a lack of confidence across all skill levels when it comes to BBN. This confidence is easily improved by a short, cost-effective teaching course. It remains to be seen if this improved confidence translates to better communication with relatives.